1967
DOI: 10.1149/1.2426662
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Silicon Nitride Films to Anodic SiO[sub 2]

Abstract: An introduction is given to the principles underlying the anodization of pre‐existing dielectric films. In the case of amorphous silicon nitride films on a silicon substrate it is shown that conversion of the nitride film to anodic SiO2 occurs by oxygen ions reacting with the nitrogen, the latter being evolved from the film as N2 or as a nitrogen oxygen compound. The process has been applied to the opening of windows in normalSi/SiO2/Si3N4 structures. Nitride films up to 1000Aå thick can be rendered solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The etch solution was renewed for each etch step to reduce effects of depletion. On reaching the SisN4 interface, the etch rate changes almost abruptly and an abrupt silicon nitride oxide interface is indicated in agreement with previous infrared transmission results (1). The break in the etch curves ( Fig.…”
Section: Calculated Conversion Carves For Small Independent Vorialisupporting
confidence: 91%
See 4 more Smart Citations
“…The etch solution was renewed for each etch step to reduce effects of depletion. On reaching the SisN4 interface, the etch rate changes almost abruptly and an abrupt silicon nitride oxide interface is indicated in agreement with previous infrared transmission results (1). The break in the etch curves ( Fig.…”
Section: Calculated Conversion Carves For Small Independent Vorialisupporting
confidence: 91%
“…One of the questions raised in the anodization of silicon nitride concerns the nature of the silicon nitride oxide interface. In the original work, Schmidt and Wonsidler concluded that the interface was abrupt from infrared absorption evidence (1). Later Tripp corroborated this evidence but, claiming that the IR method was insensitive, opted for a graded oxy-nitride interface on the basis of oxide solubility data (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations